Cost analysis of employing general practitioners within residential aged care facilities based on a prospective, stepped-wedge, cluster randomised trial - Lei Si; Andrew Robinson; Terry P. Haines; Petra Tierney; Andrew J. Palmer (BMC, 2022)
Abstract Objective To assess the impacts of changing a model of care and employing general practitioners (GPs) within residential aged care facilities (RACFs) on costs to the aged care provider (ACP) and state and federal governments of Australia. Methods This study was a cost analysis of a prospective, stepped-wedge, cluster randomised trial. All financial data from the ACP for every RACF involved, before and after implementation of the new model were obtained. Costs of hospital transfers, admissions, ambulance usage and GP consultations were calculated. Costs of new infrastructure, recruiting and training new staff were accounted for. Costs were standardised to 2019 Australian Dollars per occupied bed day (OBD). Results Implementation of the new model of care resulted in overall cost savings of $9.7 per OBD to the ACP, with increased salary costs offset by increased federal government subsidies and Medicare claims income. Costs to the federal government increased by $19.6 per OBD, driven by increases in subsides. Costs savings of $3.0 per OBD to state governments were seen, driven by decreased costs of hospital transfers. Conclusions Implementation of a model of care including GPs employed at RACFs had a mixed impact on costs depending on perspective, with overall savings to the ACP and state government perspective.